2003
DOI: 10.1038/sj.onc.1206127
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy enhances TNF-related apoptosis-inducing ligand DISC assembly in HT29 human colon cancer cells

Abstract: Cytokines such as Fas-ligand (Fas-L) and Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL) can induce human colon cancer cell apoptosis through engagement of their death domain receptors. All the cancer cells are not sensitive to these cytokines. We have shown recently that low doses of cytotoxic drugs could restore TRAIL-induced cell death in resistant colon cancer cell lines. The present work further explores the death pathway triggered by the cytotoxic drug/TRAIL combination in HT-29 colon can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 44 publications
7
85
0
Order By: Relevance
“…This concerns HT-29 colon carcinoma cells, treated with cisplatin, doxorubicin or 5-fluorouracil (5-FU) (Lacour et al, 2003) and hepatocellular carcinoma, treated with 5-FU (Ganten et al, 2004). These authors found, in common with our study, increased FADD and pro-Caspase-8/10, but not c-FLIP L content in the DISC, as well as increased Caspase-8/10 activity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This concerns HT-29 colon carcinoma cells, treated with cisplatin, doxorubicin or 5-fluorouracil (5-FU) (Lacour et al, 2003) and hepatocellular carcinoma, treated with 5-FU (Ganten et al, 2004). These authors found, in common with our study, increased FADD and pro-Caspase-8/10, but not c-FLIP L content in the DISC, as well as increased Caspase-8/10 activity.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, DNA damage can transcriptionally upregulate TRAIL-R1, TRAIL-R2 (Wu et al, 1997;Guan et al, 2001) and CD95 (Mu¨ller et al, 1998) and stimulate CD95 transport to the cell surface (Bennett et al, 1998), which may explain synergistic combined effects. However, combined effects are also observed without death receptor upregulation at the cell surface (Kim et al, 2001;Lacour et al, 2003;Vivo et al, 2003;Ganten et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Classical anticancer agents all induce apoptosis when tested on cell lines in vitro. They usually activate the intrinsic pathway to death that involves the mitochondria and downstream caspase activation, although a ligand-independent role for death receptors was also suggested (Micheau et al, 1999;Lacour et al, 2003). In multiple myeloma cells exposed to cytotoxic drugs, Mcl-1 expression specifically decreases through either synthesis blockade (Raje et al, 2005) or proteasome degradation (Zhong et al, 2005) or caspase-mediated cleavage (Gomez-Bougie et al, 2005a), depending on the stimulus, whereas Bcl-2 expression remains unchanged (Michels et al, 2005).…”
Section: Mitochondria As a Target For Treating Hematopoietic Cell Dismentioning
confidence: 99%
“…The potential of TRAIL for colorectal cancer treatment is highlighted by the ability of TRAIL to inhibit growth of xenografts of several colon carcinoma cell lines in mouse models and to cooperate with chemotherapeutic agents such as 5-fluorouracil (5-FU), cisplatin, doxorubicin and camptothecin analogue CPT-11 (Ashkenazi et al, 1999;Gliniak and Le, 1999;Lacour et al, 2001Lacour et al, , 2003Shimoyama et al, 2002). In the carcinoma cell line HT29, chemotherapeutic agents, as well as potentiating the mitochondrial amplification of the caspase cascade, enhance recruitment of the adapter protein FADD and caspase-8 to the death-inducing signal complex (DISC) (Lacour et al, 2003).…”
mentioning
confidence: 99%